Hubungan antara Imunisasi Rotavirus dengan Kejadian Diare pada Balita - Syahfira, Reisyah; Nareswari, Shinta; Berawi, Khairunnisa (Medula, 2025)
Diarrhea is a condition of defecating more than 3 times a day accompanied by a change in the consistency of the stool to liquid with or without mucus and blood that lasts less than one week. Diarrhea results in a loss of fluids and electrolytes, especially sodium and potassium, in large amounts. Fluid loss that continues and is not balanced with adequate replacement will result in dehydration. The risk of dehydration in toddlers is greater due to the inability to meet their fluid needs while their body fluid composition is large. Dehydration that is allowed to continue will result in several complications and even death. Therefore, diarrhea is one of the diseases that is the main cause of morbidity and death in children under five. One prevention of diarrhea is rotavirus immunization. Rotavirus immunization is an effort to actively create/increase a person's immunity against a disease so that if one day they are exposed to the disease they will not get sick or will only experience mild illness. This research was conducted to determine the relationship between rotavirus immunization and the incidence of diarrhea in toddlers. This research uses a literature review method with data sources from the National Center for Biotechnology Information, Google Scholar, and Science. The research year range of articles is 2018 to 2021 and articles conducted in English and Indonesian literature. The results of this literature review from the 6 articles analyzed stated that there was a relationship between rotavirus immunization and the incidence of diarrhea in toddlers.